Challenges and Solutions in Developing Eco-Friendly Electric Vehicles with Extended Range - Krisdiyanto, Aris; Dewi, Kemmala (Westscience Press, 2023)
This research investigates the challenges and solutions associated with the development and adoption of environmentally friendly electric vehicles (EVs) in Jakarta, Indonesia, a densely populated and rapidly urbanizing city facing pressing environmental and transportation issues. Employing a mixed-methods approach, this study combines quantitative surveys with qualitative interviews and focus group discussions to provide a comprehensive understanding of the dynamics influencing EV adoption. The findings reveal a relatively high level of awareness of EVs among Jakarta residents, with positive perceptions centered on environmental benefits. However, barriers such as high initial costs and concerns about charging infrastructure availability hinder adoption. Government policies, including incentives and clearer regulatory frameworks, are identified as pivotal drivers for EV adoption. Insights from government officials, industry stakeholders, and consumers emphasize the importance of collaboration to overcome infrastructure challenges and promote electric mobility. The study's recommendations aim to inform policymakers, industry players, and urban planners in their efforts to facilitate the transition to sustainable electric transportation in Jakarta.